2022
DOI: 10.1177/02683555221094642
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in ankle range of motion, dorsi and plantar flexors muscle strength and gait speed in patients with chronic venous disorders: A systematic review and meta-analysis

Abstract: Objective To verify the differences in ankle range of motion (ROM), muscle strength of dorsi and plantar flexors, and gait speed among healthy subjects, and patients with chronic venous disorders (CVD) with and without venous leg ulcer. Methods A systematic review and meta-analysis ( http://osf.io/b7n3k ) were conducted following a search of MEDLINE, Web of Science, CINAHL, LILACS, Scopus, and EMBASE databases. Results Eight papers were included. The ankle ROM was significantly lower both in dorsiflexion and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(71 reference statements)
0
1
0
1
Order By: Relevance
“…The authors could not detect significant differences in ROM between legs with confirmed CVD, but no ulcer and healthy legs [29]. A very recent meta-analysis was able to show that both, dorsiflexion, and plantarflexion is impaired in patients with VLU when comparing healthy subjects and patients with CVD without ulcer [30]. As more women are affected by CVD, also high-heeled shoes can be a predisposing factor for loosing full ankle ROM because of the pronounced plantarflexion during standing and walking.…”
Section: Ankle Range Of Motionmentioning
confidence: 89%
“…The authors could not detect significant differences in ROM between legs with confirmed CVD, but no ulcer and healthy legs [29]. A very recent meta-analysis was able to show that both, dorsiflexion, and plantarflexion is impaired in patients with VLU when comparing healthy subjects and patients with CVD without ulcer [30]. As more women are affected by CVD, also high-heeled shoes can be a predisposing factor for loosing full ankle ROM because of the pronounced plantarflexion during standing and walking.…”
Section: Ankle Range Of Motionmentioning
confidence: 89%
“…Patienten mit CVD, v. a. in höheren C-Klassen, haben eine Funktionsminderung der Wadenmuskelpumpe [49,50]. Die reduzierte Muskelkraft tritt dabei bei CVD-Patienten häufig mit einer ROM-Einschränkung und einer reduzierten Ganggeschwindigkeit auf [51]. Ist die Wadenmuskelpumpe insuffizient, bestehen größere Geschwüre als mit intakter Muskelpumpe.…”
Section: Muskuläre Einschränkungen Im Wadenbereichunclassified